Surface modified neodymium-iron-boron magnetic powder and preparation method thereof, injection molding neodymium-iron-boron composite material and application

By installing phosphide, molybdenum disulfide and polytetrafluoroethylene layers on the surface of NdFeB magnetic powder and fixing them with thermosetting resin, the problem of injection-molded NdFeB material being easily rusted and not wear-resistant is solved, and its oxidation resistance is significantly improved and wear resistance, expanding its prospects for motor rotor applications.

CN119181556APending Publication Date: 2024-12-24HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310748706.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-24

Smart Images

  • Figure CN119181556A_ABST
    Figure CN119181556A_ABST
Patent Text Reader

Abstract

The invention provides surface modified neodymium-iron-boron magnetic powder and a preparation method thereof, an injection molding neodymium-iron-boron composite material and application. The surface modified neodymium-iron-boron magnetic powder comprises neodymium-iron-boron magnetic powder, and a phosphide layer, a molybdenum disulfide and polytetrafluoroethylene layer and a thermosetting resin layer which are sequentially arranged on the surface of the neodymium-iron-boron magnetic powder from inside to outside. According to the scheme, the phosphide layer is arranged on the surface of the neodymium-iron-boron magnetic powder, the oxidation resistance of the neodymium-iron-boron magnetic powder is improved, the molybdenum disulfide and polytetrafluoroethylene layer is arranged and fixed to the surface of the neodymium-iron-boron magnetic powder through thermosetting resin, and the neodymium-iron-boron magnetic powder embedded with the wear-resistant material on the surface is obtained. And the oxidation resistance and the wear resistance of the neodymium iron boron magnetic powder are further improved. The neodymium-iron-boron magnetic powder subjected to surface modification treatment is used for preparing an injection molding neodymium-iron-boron composite material, the good magnetic performance is achieved, the wear resistance and the oxidation and rust resistance can be remarkably improved, and the neodymium-iron-boron magnetic powder has the wide application prospect in the aspect of preparing motor rotors of automobiles, household appliances and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of injection-molded magnetic composite materials, and in particular to a surface-modified NdFeB magnetic powder and a preparation method thereof, an injection-molded NdFeB composite material and applications thereof. Background Art

[0002] Permanent magnetic materials mainly include sintered permanent magnetic materials, molded permanent magnetic materials, injection molded permanent magnetic materials, etc. Injection molded permanent magnetic materials have the advantages of easy processing, high precision, good toughness, etc. In addition, they have unique advantages in preparing complex shapes and integrated forming devices. Injection molded permanent magnetic materials have been widely used in the fields of automobiles, home appliances, office supplies, industrial machinery and children's toys.

[0003] Injection molded permanent magnet materials mainly include injection molded ferrite and injection molded NdFeB. The magnetic energy product of injection molded NdFeB material is significantly higher than that of injection molded ferrite, and the prepared magnetic rotor has higher power and speed. Therefore, injection molded NdFeB has great application potential in the thermal management system, lubrication system, and air pressure system of new energy vehicles. At present, injection molded NdFeB materials still have problems such as easy rusting, poor wear resistance, and high price, which limits their wide application.

[0004] The conventional solution is to directly add carbon fiber (1.6g / cm 3 ), polytetrafluoroethylene (2.2g / cm 3 ), MoS2 (4.8 g / cm 3 ), graphite (2.1g / cm 3 ) and other wear-resistant materials. Due to the very high density of NdFeB magnetic powder (about 7.5g / cm 3 ), the particles are very large (the average particle size is up to 200 microns), which is much higher than the density and particle size of conventional wear-resistant materials (1-10 microns). The wear-resistant materials will float on the upper layer of NdFeB magnetic powder and agglomerate together. Therefore, it is difficult to prepare a uniform composite material by conventional methods, and it is also impossible to wrap NdFeB magnetic powder with wear-resistant materials, resulting in unsatisfactory wear resistance of the composite material.

[0005] A Chinese patent application (CN115521618A) reports a conductive wear-resistant polyphenylene sulfide material, which uses linear polyphenylene sulfide resin as a matrix, fills with conductive material chopped carbon fiber and graphite, special wear-resistant additives, polytetrafluoroethylene and a small amount of lubricants, antioxidants and coupling agents and other auxiliary additives, and obtains a conductive wear-resistant polyphenylene sulfide material with good wear resistance and conductivity through a special extrusion process. However, the wear-resistant polyphenylene sulfide material does not have magnetism.

[0006] Chinese patent application (CN114539772A) reported a highly wear-resistant polyphenylene sulfide magnetic material and its preparation method, which comprises the following components by weight: 13.5-20.6 parts of PPS resin, 50-56 parts of magnetic powder, 10-14 parts of PTFE powder, 3-4 parts of nanoparticles, 0.5-0.6 parts of silane coupling agent, 1-1.6 parts of antioxidant, 1-1.6 parts of lubricant and 1-1.6 parts of plasticizer; when preparing the magnetic material, the magnetic powder is modified in advance, and the modified magnetic powder and PPS resin are used to prepare magnetic masterbatch, and then the magnetic masterbatch is added to the side feed port of the extruder, and the uniformly mixed PPS resin, PTFE powder, nanoparticles, antioxidant, plasticizer and lubricant are added to the main feed port of the extruder for melt blending and extrusion granulation. However, the magnetic properties of the composite material prepared by this method are low, and the process is complicated and the cost is high.

[0007] As a second best option, people adopted the method of embedding bearing sleeves, that is, using graphite sleeves or alumina sleeves to isolate the NdFeB composite materials from the metal bearings at the main friction position of the injection molded NdFeB device, and performing special anti-rust treatment on the injection molded NdFeB products. This greatly increased the production process and cost, and also made it difficult to recycle and reuse the products, weakening the market competitiveness of injection molded NdFeB composite materials. Summary of the invention

[0008] The main purpose of the present invention is to provide a surface modified NdFeB magnetic powder and its preparation method, an injection molded NdFeB composite material and its application, so as to solve the problem that the traditional injection molded magnetic polyphenylene sulfide composite material in the prior art is not wear-resistant and easy to oxidize and rust.

[0009] In order to achieve the above-mentioned object, according to one aspect of the present invention, a surface modified NdFeB magnetic powder is provided, which comprises: NdFeB magnetic powder and a phosphide layer, a molybdenum disulfide and a polytetrafluoroethylene layer and a thermosetting resin layer sequentially arranged on the surface of the NdFeB magnetic powder from the inside to the outside.

[0010] Further, the NdFeB magnetic powder includes any one or more of rapidly quenched NdFeB powder and recycled crushed NdFeB powder. Preferably, the average particle size of the NdFeB magnetic powder is 20-200 microns.

[0011] Preferably, the phosphide layer is obtained by corroding or depositing any one or more of phosphoric acid and phosphate compounds on the surface of NdFeB magnetic powder;

[0012] Preferably, the weight ratio of NdFeB magnetic powder to phosphide layer is 100:0.2-2.

[0013] Further, the molybdenum disulfide is in the form of flakes, preferably, the average particle size of the molybdenum disulfide is 1-10 microns, and preferably the weight ratio of the neodymium iron boron magnetic powder to the molybdenum disulfide is 100:2-10;

[0014] And / or, the polytetrafluoroethylene is spherical or quasi-spherical, preferably, the average particle size of the polytetrafluoroethylene is 1-100 μm, preferably, the polytetrafluoroethylene is any one or more of suspended polytetrafluoroethylene powder and crushed polytetrafluoroethylene powder, preferably, the weight ratio of neodymium iron boron magnetic powder to polytetrafluoroethylene is 100:2-10;

[0015] Preferably, the surface of the polytetrafluoroethylene has a phosphide.

[0016] Furthermore, the thermosetting resin is selected from any one or more of epoxy resin, phenolic resin and unsaturated resin. Preferably, the weight ratio of NdFeB magnetic powder to thermosetting resin is 100:0.2-2.

[0017] According to another aspect of the present invention, there is provided a method for preparing any of the above-mentioned surface-modified NdFeB magnetic powders, the preparation method comprising: step S1, mixing NdFeB magnetic powder, polytetrafluoroethylene and a phosphide solution to obtain phosphide layer-coated NdFeB magnetic powder and polytetrafluoroethylene powder; step S2, mixing molybdenum disulfide with the phosphide layer-coated NdFeB magnetic powder and polytetrafluoroethylene powder to obtain NdFeB magnetic powder with molybdenum disulfide and polytetrafluoroethylene adsorbed on the surface; step S3, mixing a thermosetting resin solution with the NdFeB magnetic powder with molybdenum disulfide and polytetrafluoroethylene adsorbed on the surface, and performing a curing reaction to obtain surface-modified NdFeB magnetic powder.

[0018] Further, in step S1, the temperature of the mixing treatment is 50-120°C;

[0019] Preferably, step S1 comprises: mixing NdFeB magnetic powder and polytetrafluoroethylene, adding phosphide solution under the protection of inert gas to react; preferably, the reaction time is 30-60 minutes; preferably, the mixing and reaction are carried out in a mixer, and further preferably, the rotation speed of the mixer is 100-500 r / min;

[0020] Preferably, the solvent of the phosphide solution is any one or more of acetone, ethanol, methanol, isopropanol and water, and further the content of phosphide in the phosphide solution is 5-30wt%.

[0021] Further, in step S2, the mixing time is 30-60 min, and preferably, the rotation speed of the mixing device is 100-500 r / min;

[0022] And / or, in step S3, the curing reaction time is 30-60 minutes;

[0023] Preferably, the solvent of the thermosetting resin solution is any one or more of butanone, ethyl acetate, dichloromethane and acetone. More preferably, the content of the thermosetting resin in the thermosetting resin solution is 5 to 30 wt %.

[0024] According to another aspect of the present application, an injection molded NdFeB composite material is provided, which is prepared from the following raw materials: polyphenylene sulfide, a lubricant, a coupling agent, a compatibilizer, an antioxidant and surface modified NdFeB magnetic powder; wherein the surface modified NdFeB magnetic powder is any one of the above-mentioned surface modified NdFeB magnetic powders or surface modified NdFeB magnetic powders prepared by any of the above-mentioned preparation methods.

[0025] Further, the raw materials include, by weight, 100 parts of surface-modified NdFeB magnetic powder, 5-30 parts of polyphenylene sulfide, 0.1-1 parts of lubricant, 0.2-2 parts of coupling agent, 0.2-2 parts of compatibilizer and 0.1-1 parts of antioxidant;

[0026] Preferably, the polyphenylene sulfide is linear polyphenylene sulfide, and more preferably the melt index of the polyphenylene sulfide is 300-5000 g / 10 min;

[0027] Preferably, the lubricant is one or more of lithium stearate, zinc stearate, pentaerythritol stearate and artificial wax;

[0028] Preferably, the coupling agent is one or more of a silane coupling agent, a titanate coupling agent and an aluminate coupling agent;

[0029] Preferably, the compatibilizer is any one or more of maleic anhydride grafted POE, maleic anhydride grafted SEBS and ethylene-methyl acrylate-glycidyl methacrylate terpolymer;

[0030] Preferably, the antioxidant is any one or more of antioxidant 1010 , antioxidant 168 , antioxidant 1076 and antioxidant 1098 .

[0031] According to another aspect of the present application, there is provided a use of any one of the above-mentioned injection-molded NdFeB composite materials in a motor rotor.

[0032] The technical scheme of the present invention is applied, by setting a phosphide layer on the surface of NdFeB magnetic powder, the hydroxyl content on the surface of the magnetic powder is increased, the anti-oxidation ability of NdFeB magnetic powder is improved, and by setting a molybdenum disulfide and polytetrafluoroethylene layer, polytetrafluoroethylene powder and molybdenum disulfide powder are adsorbed on the surface of NdFeB, and fixed on the surface of NdFeB magnetic powder by thermosetting resin, to obtain NdFeB magnetic powder with wear-resistant material embedded on the surface, further improving the anti-oxidation ability and wear resistance of NdFeB magnetic powder. The surface-modified NdFeB magnetic powder is used to prepare injection-molded NdFeB composite materials, which not only has good magnetic properties, but also can significantly improve wear resistance and anti-oxidation and rust resistance, and has broad application prospects in the preparation of motor rotors for automobiles, home appliances, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0034] Figure 1 A schematic structural diagram of surface-modified NdFeB magnetic powder according to an embodiment of the present invention is shown.

[0035] The above drawings include the following reference numerals: 100, NdFeB magnetic powder; 110, phosphide layer; 121, polytetrafluoroethylene; 122, molybdenum disulfide; 130, thermosetting resin. DETAILED DESCRIPTION

[0036] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0037] As analyzed in the background technology of this application, there are problems in the prior art that traditional injection molded magnetic polyphenylene sulfide composite materials are not wear-resistant and are easily oxidized and rusted. In order to solve this problem, this application provides a surface-modified NdFeB magnetic powder and a preparation method thereof, an injection molded NdFeB composite material and its application.

[0038] According to a typical embodiment of the present application, a surface-modified NdFeB magnetic powder is provided, which comprises: NdFeB magnetic powder and a phosphide layer, a molybdenum disulfide and polytetrafluoroethylene layer and a thermosetting resin layer sequentially arranged on the surface of the NdFeB magnetic powder from the inside to the outside.

[0039] By setting a phosphide layer on the surface of NdFeB magnetic powder, the hydroxyl content on the surface of the magnetic powder is increased, and the anti-oxidation ability of NdFeB magnetic powder is improved. By setting a molybdenum disulfide and polytetrafluoroethylene layer, polytetrafluoroethylene powder and molybdenum disulfide powder are adsorbed on the surface of NdFeB, and fixed on the surface of NdFeB magnetic powder by thermosetting resin, NdFeB magnetic powder with wear-resistant material embedded on the surface is obtained, and the anti-oxidation ability and wear resistance of NdFeB magnetic powder are further improved. The surface-modified NdFeB magnetic powder is used to prepare injection-molded NdFeB composite materials, which can significantly improve the wear resistance and anti-oxidation and rust resistance, and has broad application prospects in the preparation of motor rotors for automobiles, home appliances, etc.

[0040] The above-mentioned NdFeB magnetic powder for surface treatment as raw material can be selected from the existing technology. For example, the NdFeB magnetic powder includes any one or more of rapidly quenched NdFeB powder and recycled crushed NdFeB powder. When the average particle size of the NdFeB magnetic powder is 20-200 microns, the application effect is better; further preferably, the average particle size of the NdFeB magnetic powder is 40-200 microns, and more preferably 50 to 150 microns.

[0041] Preferably, the phosphide layer is obtained by corroding or depositing any one or more of phosphoric acid and phosphate compounds on the surface of NdFeB magnetic powder, wherein the selection of phosphate can refer to the prior art, and there is no special requirement in this application; preferably, the weight ratio of NdFeB magnetic powder to phosphide layer is 100:0.2-2, which has good antioxidant ability and magnetic properties.

[0042] In order to improve the bonding ability of molybdenum disulfide and magnetic powder, give full play to the friction reduction function of molybdenum disulfide, and further improve the wear resistance and stability of surface-modified NdFeB magnetic powder, in some embodiments of the present application, molybdenum disulfide is in the form of flakes. Preferably, the average particle size of molybdenum disulfide is 1-10 microns, which significantly improves the wear resistance and stability of surface-modified NdFeB magnetic powder, and more preferably 3-8 microns. Preferably, the weight ratio of NdFeB magnetic powder to molybdenum disulfide is 100:2-10.

[0043] In some embodiments of the present application, polytetrafluoroethylene is spherical or quasi-spherical, which can further improve the wear resistance of the surface-modified NdFeB magnetic powder. Preferably, the average particle size of polytetrafluoroethylene is 1-100 microns, more preferably 5-80 microns, and further preferably 10-70 microns, such as 10 microns, 15 microns, 20 microns, 25 microns, 30 microns, 35 microns, 40 microns, 45 microns, 50 microns, 55 microns, 60 microns, 65 microns, 70 microns or any range between the two, which is more effective in improving the performance of the magnetic powder. Preferably, polytetrafluoroethylene is any one or more of suspended polytetrafluoroethylene powder and polytetrafluoroethylene crushed powder, and the weight ratio of NdFeB magnetic powder to polytetrafluoroethylene is preferably 100:2-10, which significantly improves the wear resistance of the surface-modified NdFeB magnetic powder.

[0044] In some embodiments of the present application, the surface of polytetrafluoroethylene has phosphide, and the structure of the surface-modified NdFeB magnetic powder is as follows: Figure 1 As shown, there is a phosphide layer 110 on the surface of the NdFeB magnetic powder 100, and there is also a phosphide layer 110 on the surface of the polytetrafluoroethylene 121. Due to the effect of the phosphide, the polytetrafluoroethylene 121 can have a better bonding force with the NdFeB magnetic powder 100 and the thermosetting resin 130, which can not only improve the wear resistance of the magnetic powder, but also firmly bond with the magnetic powder and is not prone to powder falling; at the same time, in combination with molybdenum disulfide 122, the wear resistance and oxidation resistance of the surface modified NdFeB magnetic powder are significantly improved.

[0045] The above-mentioned thermosetting resin can be selected from the prior art without special requirements. In some embodiments of the present application, in order to improve the bonding ability of the thermosetting resin with molybdenum disulfide, polytetrafluoroethylene and phosphide, and further improve the wear resistance of the surface-modified NdFeB magnetic powder, the thermosetting resin is selected from any one or more of epoxy resin, phenolic resin and unsaturated resin. Preferably, the weight ratio of NdFeB magnetic powder to thermosetting resin is 100:0.2-2, and the performance improvement of the surface-modified NdFeB magnetic powder is more obvious.

[0046] According to another typical embodiment of the present application, a method for preparing any of the above-mentioned surface-modified NdFeB magnetic powders is provided, and the preparation method comprises: step S1, mixing NdFeB magnetic powder, polytetrafluoroethylene and a phosphide solution to obtain phosphide layer-coated NdFeB magnetic powder and polytetrafluoroethylene powder; step S2, mixing molybdenum disulfide with the phosphide layer-coated NdFeB magnetic powder and polytetrafluoroethylene powder to obtain NdFeB magnetic powder with molybdenum disulfide and polytetrafluoroethylene adsorbed on the surface; step S3, mixing a thermosetting resin solution with the NdFeB magnetic powder with molybdenum disulfide and polytetrafluoroethylene adsorbed on the surface, and performing a curing reaction to obtain surface-modified NdFeB magnetic powder.

[0047] The preparation method increases the hydroxyl content on the surface of the NdFeB magnetic powder by setting a phosphide layer on the surface of the NdFeB magnetic powder, improves the anti-oxidation ability of the NdFeB magnetic powder, and adsorbs the polytetrafluoroethylene powder and the molybdenum disulfide powder on the surface by setting a molybdenum disulfide and polytetrafluoroethylene layer, and fixes them on the surface of the NdFeB magnetic powder by a thermosetting resin, thereby obtaining the NdFeB magnetic powder with the surface inlaid with wear-resistant materials. In addition, polytetrafluoroethylene is added to the system before the phosphide layer is formed, so that the surface of polytetrafluoroethylene is slightly corroded under the action of the phosphide, thereby improving the bonding ability with the magnetic powder and the thermosetting resin, which can not only improve the wear resistance of the NdFeB magnetic powder, but also make the polytetrafluoroethylene firmly bonded to the magnetic powder, and it is not easy to fall off the powder; further, during the mixing process, under the action of friction between polytetrafluoroethylene and magnetic powder, the molybdenum disulfide can be fully dispersed and peeled off, thereby improving its anti-friction and anti-rust functions. Using this surface-modified NdFeB magnetic powder to prepare injection-molded NdFeB materials can significantly improve wear resistance and oxidation and rust resistance, and has broad application prospects in the preparation of motor rotors for automobiles, home appliances, etc.

[0048] In some embodiments of the present application, in the above step S1, the temperature of the mixing treatment is 50-120°C, which is conducive to the corrosion and bonding of the phosphide to the magnetic powder and polytetrafluoroethylene, and promotes the rapid volatilization of the solvent in the phosphide solution, so that a portion of the phosphide is deposited on the surface of the NdFeB magnetic powder and polytetrafluoroethylene.

[0049] In some typical embodiments of the present application, the above step S1 includes: mixing NdFeB magnetic powder and polytetrafluoroethylene, adding a phosphide solution under the protection of an inert gas to react, so that the phosphide is corroded and deposited on the surface of the NdFeB magnetic powder and polytetrafluoroethylene to obtain a phosphide layer coated NdFeB magnetic powder, and first mixing the NdFeB magnetic powder and polytetrafluoroethylene and then adding the phosphide solution, so that the polytetrafluoroethylene can be distributed more evenly on the surface of the NdFeB magnetic powder, and a more uniform phosphating layer can be formed, thereby further improving the comprehensive performance of the surface modified magnetic powder. Preferably, the reaction time is 30-60min; preferably, the mixing and reaction are carried out in a mixer, and further preferably, the speed of the mixer is 100-500r / min, so that a more uniform phosphide layer is formed on the surface of the magnetic powder, and the distribution of polytetrafluoroethylene is more uniform. Preferably, the solvent of the phosphide solution is any one or more of acetone, ethanol, methanol, isopropanol and water, and further the content of the phosphide in the phosphide solution is 5 to 30 wt %, which is conducive to better dispersion of the phosphide while taking into account the removal efficiency of the solvent.

[0050] In some embodiments of the present application, in order to fully open the lamellae of flaky molybdenum disulfide, further exert its antifriction performance and improve its utilization rate, in step S2, the mixing time is 30-60min, and illustratively, the mixing time can be 30min, 35min, 40min, 45min, 50min, 55min, 60min or any range between the two. Since there are a large amount of magnetic powder and polytetrafluoroethylene powder in the system, the lamellae in the molybdenum disulfide can be peeled off and dispersed under the action of friction during the mixing process, further improving its antifriction function. The above mixing time can make the molybdenum disulfide lamellae dispersed more fully, and the performance improvement of the magnetic powder is more obvious. Preferably, the rotation speed of the device for performing the above mixing is 100-500r / min, which has a more obvious performance-promoting effect on molybdenum disulfide.

[0051] In the above step S3, a thermosetting resin solution is added and mixed with the NdFeB magnetic powder with molybdenum disulfide and polytetrafluoroethylene adsorbed on the surface, so as to fix the molybdenum disulfide and polytetrafluoroethylene on the surface of the NdFeB magnetic powder. The curing conditions can be determined according to the type of thermosetting resin selected, and will not be described in detail here.

[0052] In some embodiments of the present application, in the above step S3, the curing reaction time is 30-60 minutes, and the curing effect is better.

[0053] The solvent of the thermosetting resin solution can be selected from the prior art. In some embodiments of the present application, the solvent of the thermosetting resin solution is any one or more of butanone, ethyl acetate, dichloromethane, and acetone. In order to take into account both the dispersion effect of the thermosetting resin and the use efficiency of the solvent, the content of the thermosetting resin in the thermosetting resin solution is preferably 5 to 30 wt%.

[0054] In some typical embodiments of the present application, in order to facilitate the implementation of the process, the above steps S1 to S3 are all carried out in a mixer, preferably in the same mixer, which is convenient for implementation and can achieve good implementation results.

[0055] According to another typical embodiment of the present application, an injection molded NdFeB composite material is provided, which is prepared from the following raw materials: polyphenylene sulfide, a lubricant, a coupling agent, a compatibilizer, an antioxidant and surface modified NdFeB magnetic powder; wherein the surface modified NdFeB magnetic powder is any one of the above-mentioned surface modified NdFeB magnetic powders or a surface modified NdFeB magnetic powder prepared by any of the above-mentioned preparation methods.

[0056] The surface-modified NdFeB magnetic powder increases the hydroxyl content on the surface of the NdFeB magnetic powder by setting a phosphide layer on the surface of the NdFeB magnetic powder, improves the oxidation resistance of the NdFeB magnetic powder, and adsorbs the polytetrafluoroethylene powder and molybdenum disulfide powder on the surface of the NdFeB magnetic powder by setting a molybdenum disulfide and polytetrafluoroethylene layer, and fixes them on the surface of the NdFeB magnetic powder by a thermosetting resin, thereby obtaining NdFeB magnetic powder with a wear-resistant material embedded on the surface. The surface-modified NdFeB magnetic powder is used to prepare injection-molded NdFeB materials, which can significantly improve the wear resistance and oxidation resistance and rust resistance, and has broad application prospects in the preparation of motor rotors for automobiles, home appliances, etc.

[0057] In some embodiments of the present application, in order to better exert the synergistic effect of the components, the raw materials include, by weight, 100 parts of surface modified NdFeB magnetic powder, 5-30 parts of polyphenylene sulfide, 0.1-1 parts of lubricant, 0.2-2 parts of coupling agent, 0.2-2 parts of compatibilizer and 0.1-1 parts of antioxidant.

[0058] The specific selection of polyphenylene sulfide, lubricant, coupling agent, compatibilizer and antioxidant can refer to the existing technology, and this application has no special requirements.

[0059] In some preferred embodiments of the present application, the polyphenylene sulfide is linear polyphenylene sulfide, and the melt index of the polyphenylene sulfide is preferably 300-5000 g / 10 min, which is beneficial to improving the comprehensive performance of the injection molded NdFeB composite material.

[0060] In some preferred embodiments of the present application, the lubricant is one or more of lithium stearate, zinc stearate, pentaerythritol stearate, and artificial wax, which can further improve the comprehensive performance of the injection molded NdFeB composite material.

[0061] In some embodiments of the present application, the coupling agent is one or more of a silane coupling agent, a titanate coupling agent and an aluminate coupling agent, which has a good match with the surface-modified NdFeB magnetic powder, the main component of the raw materials of the present application, and helps to further improve its mechanical properties.

[0062] There is no special requirement for the compatibilizer. As examples, any one or more of maleic anhydride grafted POE, maleic anhydride grafted SEBS and ethylene-methyl acrylate-glycidyl methacrylate terpolymer may be cited.

[0063] The antioxidant may be selected from the prior art, such as any one or more of antioxidant 1010 , antioxidant 168 , antioxidant 1076 and antioxidant 1098 .

[0064] The preparation method of the above-mentioned injection molded NdFeB composite material can refer to the prior art without special restrictions. Exemplarily, the preparation method is as follows: add the surface modified NdFeB magnetic powder into a mixer, then add polyphenylene sulfide, lubricant, coupling agent, compatibilizer, antioxidant, dehumidify, pre-mix, and then melt blend and granulate in a twin-screw extruder to obtain a composite material, and the processing temperature is 280-330°C.

[0065] Those skilled in the art may also add auxiliary agents to the above raw materials according to actual needs to enable them to achieve corresponding functions. The types of auxiliary agents can be selected from the prior art and will not be described in detail here.

[0066] According to another typical embodiment of the present application, the application of any of the above-mentioned injection-molded NdFeB composite materials in motor rotors is provided. The above-mentioned surface-modified NdFeB magnetic powder is used to prepare injection-molded NdFeB materials, which can significantly improve wear resistance and oxidation resistance and rust resistance, and has broad application prospects in the preparation of motor rotors for automobiles, home appliances, etc.

[0067] The beneficial effects that can be achieved by the present application will be further illustrated below in combination with embodiments and comparative examples.

[0068] Example 1

[0069] The weight fractions of each raw material in the present embodiment are as follows:

[0070] 100 parts of rapid quenching NdFeB powder (average particle size 50 microns)

[0071] Composite phosphating liquid (German Henkel M-FE7760) 0.2 parts

[0072] 2 parts of polytetrafluoroethylene powder (DuPont MP1400, USA, average particle size 10 microns)

[0073] 2 parts of flake molybdenum disulfide powder (made in Japan, average particle size 3.5 microns)

[0074] Thermosetting epoxy resin (E51 and crosslinking agent) 0.2 parts

[0075] Polyphenylene sulfide (Toray M2888, melt index 600g / 10min) 5 parts

[0076] Lithium stearate 0.1 part

[0077] KH560 silane coupling agent 0.2 parts

[0078] Maleic anhydride grafted POE compatibilizer (DuPont GR216) 0.2 parts

[0079] 1010 Antioxidant 0.1 part

[0080] The preparation steps are as follows:

[0081] (1) Add 100 parts of NdFeB magnetic powder and 2 parts of polytetrafluoroethylene powder into a high-speed mixer, set the temperature to 100 degrees, set the speed to 300 r / min (maintain the speed and temperature in the subsequent steps), and introduce nitrogen protection. Then add 0.2 parts of composite phosphating solution and solvent (alcohol, the content of phosphide in the mixed solution is 20%), and react for 40 minutes to obtain phosphide-coated NdFeB magnetic powder and phosphide-coated polytetrafluoroethylene powder.

[0082] (2) Add 2 parts of flaky molybdenum disulfide powder into a mixer and mix for 45 minutes. Under the action of friction, the molybdenum disulfide flakes are opened and adsorbed on the surface of the NdFeB magnet to obtain NdFeB magnetic powder with molybdenum disulfide and polytetrafluoroethylene adsorbed on the surface.

[0083] (3) Add 0.2 parts of thermosetting resin and solvent (acetone, the content of thermosetting resin in the mixed solution is 20%) into the mixer, and continue to react for 45 minutes to obtain wear-resistant NdFeB powder with a composite coating structure.

[0084] (4) Continue to add 5 parts of polyphenylene sulfide resin, 0.1 parts of lithium stearate, 0.2 parts of KH560 silane coupling agent, 0.2 parts of maleic anhydride grafted POE compatibilizer, and 0.1 parts of antioxidant 1010 into the mixer. Mix for 30 minutes to obtain a mixture.

[0085] (5) The temperature of the twin-screw extruder is set at 280-330° C., and the mixed materials are melt-blended and granulated in the twin-screw extruder to obtain a magnetic polyphenylene sulfide composite material.

[0086] Example 2

[0087] The weight fractions of each raw material in the present embodiment are as follows:

[0088] 100 parts of rapid quenching NdFeB powder (average particle size 50 microns)

[0089] Composite phosphating liquid (German Henkel M-FE7760) 0.5 parts

[0090] 5 parts of polytetrafluoroethylene powder (DuPont MP1400, USA, average particle size 10 microns)

[0091] 5 parts of flake molybdenum disulfide powder (made in Japan, average particle size 3.5 microns)

[0092] 1 part of thermosetting epoxy resin (E51 and crosslinking agent)

[0093] Polyphenylene sulfide (Toray M2888, melt index 600g / 10min) 10 parts

[0094] 0.5 parts of lithium stearate

[0095] KH560 silane coupling agent 1 part

[0096] Maleic anhydride grafted POE compatibilizer (DuPont GR216) 1 part

[0097] 1010 Antioxidant 0.5 parts

[0098] The preparation steps are the same as those in Example 1.

[0099] Example 3

[0100] The weight fractions of each raw material in the present embodiment are as follows:

[0101] 100 parts of rapid quenching NdFeB powder (average particle size 50 microns)

[0102] 1.5 parts of composite phosphating liquid (German Henkel M-FE7760)

[0103] 8 parts of polytetrafluoroethylene powder (DuPont MP1400, average particle size 10 microns)

[0104] 8 parts of flake molybdenum disulfide powder (made in Japan, average particle size 3.5 microns)

[0105] 1.5 parts of thermosetting epoxy resin (E51 and crosslinking agent)

[0106] Polyphenylene sulfide (Toray M2888, melt index 600g / 10min) 20 parts

[0107] 0.8 parts of lithium stearate

[0108] KH560 silane coupling agent 1.5 parts

[0109] Maleic anhydride grafted POE compatibilizer (DuPont GR216) 1.5 parts

[0110] 1010 Antioxidant 0.8 parts

[0111] The preparation steps are the same as those in Example 1.

[0112] Example 4

[0113] The weight fractions of each raw material in the present embodiment are as follows:

[0114] 100 parts of rapid quenching NdFeB powder (average particle size 50 microns)

[0115] 2 parts of composite phosphating liquid (German Henkel M-FE7760)

[0116] 10 parts of polytetrafluoroethylene powder (DuPont MP1400, USA, average particle size 10 microns)

[0117] 10 parts of flake molybdenum disulfide powder (made in Japan, average particle size 3.5 microns)

[0118] 2 parts of thermosetting epoxy resin (E51 and crosslinking agent)

[0119] Polyphenylene sulfide (Toray M2888, melt index 600g / 10min) 30 parts

[0120] 1 part lithium stearate

[0121] KH560 silane coupling agent 2 parts

[0122] Maleic anhydride grafted POE compatibilizer (DuPont GR216) 2 parts

[0123] 1010 Antioxidant 1 part

[0124] The preparation steps are the same as those in Example 1.

[0125] Example 5

[0126] The difference from Example 2 is that in step (2), the mixing time is 15 minutes.

[0127] Example 6

[0128] The difference from Example 2 is that the average particle size of the rapidly quenched NdFeB powder is 20 microns.

[0129] Example 7

[0130] The difference from Example 2 is that the average particle size of the rapidly quenched NdFeB powder is 200 microns.

[0131] Example 8

[0132] The difference from Example 2 is that the average particle size of the flaky molybdenum disulfide powder is 1 micron.

[0133] Example 9

[0134] The difference from Example 2 is that the average particle size of the flaky molybdenum disulfide powder is 10 microns.

[0135] Example 10

[0136] The difference from Example 2 is that the average particle size of the flaky molybdenum disulfide powder is 15 microns.

[0137] Embodiment 11

[0138] The difference from Example 2 is that the average particle size of the polytetrafluoroethylene powder is 1 micron.

[0139] Example 12

[0140] The difference from Example 2 is that the average particle size of the polytetrafluoroethylene powder is 100 microns.

[0141] Comparative Example 1

[0142] The raw materials and mass fractions of this comparative example are as follows:

[0143] 100 parts of rapid quenching NdFeB powder (average particle size 50 microns)

[0144] Polyphenylene sulfide (Toray M2888, melt index 600g / 10min) 10 parts

[0145] 0.5 parts of lithium stearate

[0146] KH560 silane coupling agent 1 part

[0147] Maleic anhydride grafted POE compatibilizer (DuPont GR216) 1 part

[0148] 1010 Antioxidant 0.5 parts

[0149] The preparation steps are as follows:

[0150] (1) Add 100 parts of NdFeB magnetic powder into a high-speed mixer, set the temperature to 100 degrees, the speed to 300 r / min, and introduce nitrogen protection.

[0151] (2) Add 10 parts of polyphenylene sulfide resin, 0.5 parts of lithium stearate, 1 part of KH560 silane coupling agent, 1 part of maleic anhydride grafted POE compatibilizer, and 0.5 parts of antioxidant 1010 into a mixer and mix for 30 minutes to obtain a mixture.

[0152] (3) The temperature of the twin-screw extruder is set at 280-330° C., and the mixed materials are melt-blended and granulated in the twin-screw extruder to obtain a magnetic polyphenylene sulfide composite material.

[0153] Comparative Example 2

[0154] The raw materials are exactly the same as those in Example 1, and the preparation steps of the magnetic polyphenylene sulfide composite material are as follows:

[0155] (1) Add 100 parts of NdFeB magnetic powder to a high-speed mixer, set the temperature to 100 degrees, set the speed to 300 r / min, and introduce nitrogen protection. Then add 0.2 parts of composite phosphating solution and solvent (alcohol, the content of phosphide in the mixed solution is 20%), and react for 40 minutes to obtain phosphide-coated NdFeB magnetic powder.

[0156] (2) Add 2 parts of flaky molybdenum disulfide powder and 2 parts of polytetrafluoroethylene powder into a mixer and mix for 45 minutes.

[0157] (3) Add 0.2 parts of thermosetting resin and solvent (acetone, the content of thermosetting resin in the mixed solution is 20%) into the mixer, and continue to react for 45 minutes to obtain wear-resistant NdFeB powder with a composite coating structure.

[0158] (4) Continue to add 5 parts of polyphenylene sulfide resin, 0.1 parts of lithium stearate, 0.2 parts of KH560 silane coupling agent, 0.2 parts of maleic anhydride grafted POE compatibilizer, and 0.1 parts of antioxidant 1010 into the mixer. Mix for 30 minutes to obtain a mixture.

[0159] (5) The temperature of the twin-screw extruder is set at 280-330° C., and the mixed materials are melt-blended and granulated in the twin-screw extruder to obtain a magnetic polyphenylene sulfide composite material.

[0160] During the experiment, it was found that the polytetrafluoroethylene powder did not combine well with polyphenylene sulfide, and the polytetrafluoroethylene powder easily fell off the surface of the composite material.

[0161] Comparative Example 3

[0162] The difference from Example 2 is that the raw material does not contain polytetrafluoroethylene. Accordingly, in step (1), after adding the NdFeB magnetic powder into the high-speed mixer, the composite phosphating solution is added. The parameters of the mixer and the subsequent process are the same as those in Example 2.

[0163] Comparative Example 4

[0164] The difference from Example 2 is that the flaky molybdenum disulfide powder is replaced by the same mass fraction of flaky graphite.

[0165] Comparative Example 5

[0166] The difference from Example 2 is that the raw material does not contain flaky molybdenum disulfide, and accordingly, the preparation method skips step (2).

[0167] The magnetic polyphenylene sulfide composite materials prepared in the above examples and comparative examples were subjected to performance tests, and the test results are shown in Table 1 below. Among them, the remanence, intrinsic coercive force, and magnetic energy product were tested according to GB / T 24270-2009, the tensile strength of the composite material was tested according to GB / T1040.2-2006, the wear amount was the wear amount at 100,000 revolutions according to GBT 5478-2008 standard, and the rust area ratio was the ratio of the rust area to the total area of ​​the prepared magnetic polyphenylene sulfide composite material sample after a 48-hour salt spray test, representing the severity of the rust of the material, and the salt spray test was conducted according to the national standard GB / T10125-2012.

[0168] Table 1

[0169]

[0170]

[0171] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: the preparation method of the present application improves the anti-oxidation and anti-rust capabilities of the NdFeB magnetic powder by setting a phosphide layer on the surface of the NdFeB magnetic powder, and polytetrafluoroethylene is added to the system before the magnetic powder forms a phosphide layer, which can cause the surface of polytetrafluoroethylene to be slightly corroded by the phosphide, thereby improving the bonding ability of polytetrafluoroethylene with the magnetic powder and the thermosetting resin, which not only improves the wear resistance of the NdFeB magnetic powder, but also makes the polytetrafluoroethylene firmly bonded to the magnetic powder, and is not prone to powder falling; further, during the mixing process, the molybdenum disulfide is fully dispersed and peeled off under the action of friction, thereby improving its friction reduction function.

[0172] By setting up molybdenum disulfide and polytetrafluoroethylene layers, polytetrafluoroethylene powder and molybdenum disulfide powder are adsorbed on the surface of magnetic powder, and the wear-resistant agent is fixed on the surface of NdFeB magnetic powder by thermosetting resin, so as to obtain NdFeB magnetic powder with wear-resistant material embedded on the surface. Under the wrapping of molybdenum disulfide, polytetrafluoroethylene and thermosetting resin, the anti-oxidation and rust resistance and wear resistance of NdFeB magnetic powder are significantly improved. The NdFeB magnetic powder with wear-resistant material embedded on the surface is mixed with polyphenylene sulfide, additives and the like to obtain an injection-molded NdFeB composite material, which has excellent wear resistance and anti-oxidation and rust resistance. It has broad application prospects in the preparation of motor rotors for automobiles, home appliances, etc.

[0173] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A surface modified NdFeB magnetic powder, characterized in that: include: NdFeB magnetic powder and a phosphide layer, a molybdenum disulfide layer, a polytetrafluoroethylene layer and a thermosetting resin layer which are sequentially arranged on the surface of the NdFeB magnetic powder from the inside to the outside.

2. The surface modified NdFeB magnetic powder according to claim 1, characterized in that: The NdFeB magnetic powder includes any one or more of rapidly quenched NdFeB powder and recycled crushed NdFeB powder. Preferably, the average particle size of the NdFeB magnetic powder is 20-200 microns. Preferably, the phosphide layer is obtained by corroding or depositing any one or more of phosphoric acid and phosphate compounds on the surface of the NdFeB magnetic powder; Preferably, the weight ratio of the NdFeB magnetic powder to the phosphide layer is 100:0.2-2.

3. The surface modified NdFeB magnetic powder according to claim 1, characterized in that: The molybdenum disulfide is in the form of flakes. Preferably, the average particle size of the molybdenum disulfide is 1-10 microns. Preferably, the weight ratio of the NdFeB magnetic powder to the molybdenum disulfide is 100:2-10. And / or, the polytetrafluoroethylene is spherical or quasi-spherical, preferably, the average particle size of the polytetrafluoroethylene is 1-100 μm, preferably, the polytetrafluoroethylene is any one or more of suspended polytetrafluoroethylene powder and crushed polytetrafluoroethylene powder, and preferably, the weight ratio of the neodymium iron boron magnetic powder to the polytetrafluoroethylene is 100:2-10; Preferably, the surface of the polytetrafluoroethylene has phosphide.

4. The surface modified NdFeB magnetic powder according to claim 1, characterized in that: The thermosetting resin is selected from any one or more of epoxy resin, phenolic resin and unsaturated resin. Preferably, the weight ratio of the NdFeB magnetic powder to the thermosetting resin is 100:0.2-2.

5. A method for preparing the surface-modified NdFeB magnetic powder according to any one of claims 1 to 4, characterized in that: include: Step S1, mixing the NdFeB magnetic powder, polytetrafluoroethylene and phosphide solution to obtain phosphide layer-coated NdFeB magnetic powder and polytetrafluoroethylene powder; Step S2, mixing molybdenum disulfide with the phosphide layer coated NdFeB magnetic powder and polytetrafluoroethylene powder to obtain NdFeB magnetic powder with molybdenum disulfide and polytetrafluoroethylene adsorbed on the surface; Step S3, mixing the thermosetting resin solution with the NdFeB magnetic powder with molybdenum disulfide and polytetrafluoroethylene adsorbed on the surface, and performing a curing reaction to obtain the surface-modified NdFeB magnetic powder.

6. The preparation method according to claim 5, characterized in that: In the step S1, the temperature of the mixing treatment is 50-120°C; Preferably, the step S1 comprises: mixing the NdFeB magnetic powder and polytetrafluoroethylene, adding a phosphide solution under the protection of an inert gas to react; preferably, the reaction time is 30-60 minutes; preferably, the mixing and the reaction are carried out in a mixer, and further preferably, the rotation speed of the mixer is 100-500 r / min; Preferably, the solvent of the phosphide solution is any one or more of acetone, ethanol, methanol, isopropanol and water, and further the content of the phosphide in the phosphide solution is 5-30wt%.

7. The preparation method according to claim 5, characterized in that: In the step S2, the mixing time is 30-60 min, and preferably, the rotation speed of the device for mixing is 100-500 r / min; And / or, in step S3, the curing reaction time is 30-60 minutes; Preferably, the solvent of the thermosetting resin solution is any one or more of butanone, ethyl acetate, dichloromethane and acetone. More preferably, the content of the thermosetting resin in the thermosetting resin solution is 5 to 30 wt %.

8. An injection molded NdFeB composite material, characterized in that: The surface-modified NdFeB magnetic powder is prepared from the following raw materials: polyphenylene sulfide, lubricant, coupling agent, compatibilizer, antioxidant and surface-modified NdFeB magnetic powder; wherein the surface-modified NdFeB magnetic powder is the surface-modified NdFeB magnetic powder as described in any one of claims 1 to 4 or the surface-modified NdFeB magnetic powder prepared by the preparation method as described in any one of claims 5 to 7.

9. The injection molded NdFeB composite material according to claim 8, characterized in that: In parts by weight, the raw materials include 100 parts of surface-modified NdFeB magnetic powder, 5-30 parts of polyphenylene sulfide, 0.1-1 parts of lubricant, 0.2-2 parts of coupling agent, 0.2-2 parts of compatibilizer and 0.1-1 parts of antioxidant; Preferably, the polyphenylene sulfide is linear polyphenylene sulfide, and more preferably the melt index of the polyphenylene sulfide is 300-5000 g / 10 min; Preferably, the lubricant is one or more of lithium stearate, zinc stearate, pentaerythritol stearate and artificial wax; Preferably, the coupling agent is one or more of a silane coupling agent, a titanate coupling agent and an aluminate coupling agent; Preferably, the compatibilizer is any one or more of maleic anhydride grafted POE, maleic anhydride grafted SEBS and ethylene-methyl acrylate-glycidyl methacrylate terpolymer; Preferably, the antioxidant is any one or more of antioxidant 1010, antioxidant 168, antioxidant 1076 and antioxidant 1098.

10. Use of the injection molded NdFeB composite material according to claim 8 or 9 in a motor rotor.

Citation Information

Patent Citations

  • High-wear-resistance polyphenylene sulfide magnetic material and preparation method thereof

    CN114539772A

  • Conductive wear-resistant polyphenylene sulfide material and preparation method thereof

    CN115521618A

  • Rare earth magnetic powder mixture and rare earth magnet

    CN104851541A

  • Bonded magnet and preparation method thereof

    CN107359036A

  • Thermal oxidation-resistant neodymium iron boron composite magnetic powder and preparation method thereof and application

    CN110571006A